Crowdfunding as financial option for small and medium enterprises (SMEs) in Nigeria - Kazaure, Mansur Ahmed; Abdullah, Abdul Rashid (Universiti Putra Malaysia Press, 2018)
Small and medium scale enterprises (SMEs) act as a promoter of economic development of the developed and under developed nations. Developing countries like Nigeria that, require sustainable economic growth and development must pay attention to the SMEs sectors in order to reduce unemployment, poverty and improve the standard leaving of its society. Unfortunately, in Nigeria, SMEs have underperformed despite that, 90% of the Nigerian businesses are small scales but their contribution to the Nigerian GDP is below 10%. The main reason for this low contribution of SMEs to Nigerian GDP could be attributed to poor funding, lack of management expertise and lack of access to modern technology among others, with proper finance the SMEs can acquire modern technology and employed qualified staff. Thus, this paper focuses on crowdfunding as financial option for small and medium enterprises in Nigeria. However the paper is based on conceptual framework.